The Relationship of Islamic Values and Sundaneseness in Sundanese Proverbs as Da'wah Messages - Tata Sukayat (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
The values of da'wah messages contain the essence of Islamic teachings that must be conveyed to the object of da'wah. In the da'wah process, a preacher must understand the condition and culture of the thing of his da'wah. Culture has a close relationship with Islam. One form of culture developed in Sundanese society is proverb, which can be used as moral messages in da’wah. Because Sundanese proverb are full of noble values of the nation, which are relevant to Islamic values, this study aims to analyze da'wah messages in Sundanese proverbs and describe the relationship between Islamic and Sundanese values as da'wah messages. The research method used is descriptive analysis. The data were obtained using library research techniques through several stages: heuristics, interpretation criticism, and historiography. The results of this study indicate: First, the values of da'wah messages are found in almost all Sundanese proverbs, both in aspects of humans as individual beings and humans as social beings, as well as proverb about human spirituality. Second, the relationship between Islam and Sundanese in the context of Sundanese proverbs containing Islamic values is included in the symbiotic paradigm category, like sugar and sweetness. This research implies that the noble values in Sundanese proverbs can be practised in everyday life and used to complement da'wah material suitable for the da'i to convey according to the context.